Alkaline treatments to render starch-based biodegradable polymers self-mineralizable - Leonor, I. B. (2007)
The present research aims to develop a new route for surface functionalization of biodegradable polymers. The method is based on a wet chemistry modification, resulting in etching and/or hydrolysis in order to increase the amount of polar groups, such as hydroxyl (--OH) and carboxylic (--COOH) groups on the surface of the polymer. The polymer used as substrate was a corn starch-ethylene vinyl alcohol biodegradable blend (SEVA-C). For that purpose it was used in two different types of activation: (a) calcium hydroxide solution [Ca(OH)(2)] and (b) sodium hydroxide solution (NaOH). These treatments lead to the formation carboxylic acid-rich SEVA-C surfaces. Then, the samples were soaked in simulated body fluid (SBF) for different time periods of time until 7 days. After 1 day in SBF, the surface of SEVA-C was fully covered with spherulite particles. As the soaking time increased, the particles increased and coalesced, leading to the formation of a dense and uniform layer. Furthermore, thin-film X-ray diffraction confirms that the layer formed on the surface of the polymer was an apatite-like layer. These results suggest that this rather simple treatment is a good method for surface functionalization and subsequent mineral nucleation and growth on biodegradable polymeric surfaces to be used for bone-related applications.